Reliability of quantitative echocardiography in adult sheep and goats - Hallowell, Gayle D.; Potter, Timothy J.; Bowen, I. Mark (BioMed Central, 2012)
Background Echocardiography is a non-invasive method for assessment of the ovine and caprine heart. Complete reference ranges for cardiac dimensions and time indices for both species are not currently available and reliability of these measurements has not been evaluated. The objectives for this study are to report reliability, normal cardiac dimensions and time indices in a large group of adult sheep and goats.